Waterborne polyurethane‐based dye with covalently bonded to Disperse blue 60. Issue 28 (24th December 2019) - Hu, Xianhai; Li, Mingjun; Xian, Yuxi; Liu, Xiang; Liu, Manli; Li, Gen; Hu, Pengwei; Cheng, Congliang
ABSTRACT: A series of sulfonated waterborne polyurethane‐based dyes (DB60‐SWPUs) with covalently bonded to different proportions of Disperse blue 60 (DB60) were prepared by a modified acetone process. The expected structures of DB60‐SWPUs are characterized by Fourier transform infrared spectroscopy and 1 H‐NMR spectra. The obtained DB60‐SWPUs show high viscosity and intriguing storage stability. The fluorescent performances, thermal properties, and mechanical properties of DB60‐SWPUs were characterized. Compared with DB60, the UV–vis spectra of DB60‐WPUs have obvious hypochromic shift, and the fluorescence intensities are obviously enhanced. The migration rates of DB60‐SWPUs are much lower than that of DB60. DB60‐SWPUs have thermal migration resistance and excellent color fastness. The polyester fiber dyed by DB60‐SWPUs has not only high color yield, good fracture strength, excellent breaking strength retention, but also good permeability and wrinkle resistance. Moreover, DB60‐SWPUs are polymeric dyes with water as a solvent, which are especially suitable for environmental protection. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48862. Abstract : Thermal migration models of DB60‐SWPUs (a) and DB60 + SWPU (b).